Digital Agriculture Profile: Turkey - Kropff, Wietske; Eitzinger, Anton; Hasiner, Eva; Schroeder, Kateryna; Treguer, David; Juergenliemk, Armine; Horst, Alexandra; Jarvis, Andy (Food and Agriculture Organization of the United Nations, 2021)
This Digital Agriculture Profile for Turkey leverages the expertise of in-country stakeholders to evaluate the current landscape of digital agriculture in Turkey including its key players across value chains, the main barriers they face, and the potential to overcome these barriers through the adoption of innovative technologies.